Fungi in the Global Bioeconomy: Harnessing the R Potential Across Agriculture, Medicine, Industry, and Environmental Sustainability - David Sunday Araoti* (International Journal of Fungi, 2026)
One of the most diverse and functionally versatile groups of living organisms, fungi has played a significant role in maintaining ecological balance, human well-being, agricultural production, and industrial processes. Despite their vast potential, the use of fungi systems in solving some of the most serious challenges facing the world today, such as climate change, food security, and AMR, is still in its infancy. New developments in genomics, biotechnology, and systems biology have provided new opportunities to exploit the vast potential of fungi on an unprecedented scale. Fungi have significant potential in sustainable agricultural production through interactions with plants, which improve soil quality. Fungi have vast potential in the medical field, which can be used to discover new targets for antifungal drugs, improve pathogen surveillance, and detect infectious diseases. Fungi have significant industrial potential in the production of enzymes, fermentation technologies, and the development of bio-based materials, which can be used to support sustainable industrial processes. Fungi also have significant potential in maintaining ecological balance, which can be used to support sustainability in the environment through biodegradation, bioremediation, and carbon cycling. The use of artificial intelligence in fungi systems can also be used to support sustainability in the environment through biodegradation, bioremediation, and carbon cycling. Thus, the multifaceted role of fungi in solving some of the most serious challenges facing the world today, such as climate change, food security, and AMR, can be used to unlock their vast potential in solving some of the most serious challenges facing the world today.
Keywords: Bioeconomy; Fungal Biotechnology; Genomics; Keywords: Fungi; Medical Mycology; Sustainable agriculture; artificial intelligence; bioremediation